PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII PADA MATERI MAKANAN DAN MINUMAN YANG HALAL DAN HARAM DI MTS DARUL FALAH SINGOSARI MALANG - Umu Latifah; Muhammad Hanif; Ahmad Subekti (VICRATINA, 2019)
The teacher is only guided by the material taught by the lecture method, a method that makes students easily bored in learning, so that is what causes student learning outcomes to be less than optimal.  this research was conducted at Mts Darul falah Tunjungtirto singosari, Malang.  the method of data analyst in this study is to use the percentage and the results are as follows, I before applying the make a match learning model on student learning outcomes did not reach the KKM that is 42%, after applying the make a match learning model can be known to increase student learning outcomes  in cycle 1 there was an increase of as much as 75%, while students who had not yet reached KKM were 4 students, based on the results of cycle 2 tests, it was found that an average of 89 and students graduated up to 94%,, So in this case it can be concluded that there is an increase in student learning outcomes through the application of learning models make a match in food and beverage material that is lawful and unlawful in VII Darul Falah's class.